Development of participatory empowerment process for raising youth consciousness in community development - Thongpanya, Teeraporn; Soopunyo, Weerachat; Tanpichai, Prasong; Srisuantang, Sunti (Kasetsart Journal of Social Sciences, 2016)
This action research aimed to develop a participatory empowerment process for raising youth consciousness based in Huai Mon Thong, Nakhon Pathom province, Thailand. The participants consisted of 2 groups: a group of 21 youths and a group of 10 community leaders and members. Data were collected using in-depth interviews, group discussion, participant observation and assessment on youth consciousness in community development. Data were analyzed using content analysis and descriptive statistics. In respect of the empowerment process for raising youth consciousness in community development, the community leaders and members cooperated in the empowerment process. 1) Regarding planning, youths practiced skills in thinking and doing activities through a pattern of games and participated in searching topics of community development, including planning for activity in community development. 2) Regarding action, the participants acted according to the plan and adapted this plan to different situations. The overall level of youth consciousness in community development increased. In particular, consciousness in environmental and social aspects changed from valuing to operating levels. 3) Lastly, on reflection, the participants viewed cooperation in searching demands for community development until the activity occurred as worthwhile for changing for the better the behavior of youths and community members. With regard to the research conclusion, a participatory empowerment process for raising youth consciousness in community development comprised 4 essential operations namely 1) trust, 2) encouragement, 3) autonomy, and 4) mentoring.